Shock & vibration, aircraft/aerospace, and energy harvesting, volume 9 proceedings of the 33rd IMAC, a conference and exposition on structural dynamics, 2015 - International Modal Analysis Conference Orlando, Fla.) 2015; Wicks, Alfred L.; SpringerLink (Online service (Cham Springer International Publishing, 2015)
Shock & Vibration, Aircraft/Aerospace, Energy Harvesting, Volume 9.  Proceedings of the 33rd IMAC, A Conference and Exposition on Balancing Simulation and Testing, 2015, the ninth volume of ten from the Conference brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on fundamental and applied aspects of Shock & Vibration, Aircraft/Aerospace , Energy Harvesting, including papers on: Energy Harvesting Adaptive Support Shock Calibration Operating Data Applications
Electronic reproduction.
Keywords: Structural dynamics -- Congresses; Aerospace engineering -- Congresses; Energy harvesting -- Congresses; Electronic books